Digital technology to address HIV and other sexually transmitted infection disparities: Intentions to disclose online personal health records to sex partners among students at a historically Black college. - Kevon-Mark P Jackman; Sarah Murray; Lisa Hightow-Weidman; Maria E Trent; Andrea L Wirtz; Stefan D Baral; Jacky M Jennings (PLoS ONE, 2020)
Patient portals are creating new opportunities for youth to disclose high-fidelity sexually transmitted infection (STI) laboratory test result histories to sex partners. Among an online survey sample, we describe latent constructs and other variables associated with perceived behavioral intentions to disclose STI test history using patient portals. Participants were co-ed students aged 18 to 25 years (N = 354) attending a southern United States Historically Black College and University in 2015. Three reliable latent constructs were identified by conducting psychometric analyses on 27 survey items. Latent constructs represent, a) STI test disclosure valuation beliefs, b) communication practices, and c) performance expectancy beliefs for disclosing with patient portals. Multivariable logistic regression was used to estimate the relationship of latent constructs to perceived behavioral intentions to disclose STI test history using patient portals. Approximately 14% (48/354) reported patient portal use prior to study and 59% (208/354) endorsed behavioral intentions to use patient portals to disclose STI test history. The latent construct reflecting performance expectancies of patient portals to improve communication and accuracy of disclosed test information was associated with behavioral intentions to disclose STI test histories using patient portals [adjusted odds ratio (AOR) = 1.15; 95% CI = 1.08 to 1.22; p<0.001]. Latent constructs representing communication valuation beliefs and practices were not associated with intentions. Self-reporting prior STI diagnosis was also associated with intentions to disclose using patient portals (AOR = 2.84; 95% CI = 1.15 to 6.96; p = 0.02). Point of care messages focused on improvements to validating test results, communication, and empowerment, may be an effective strategy to support the adoption of patient portals for STI prevention among populations of college-aged Black youth.